Organizational culture empowering nurses an residents in nursing homes - Herold-Majumdar, Astrid; Marijic, Pavo; Stemmer, Renate (Advances in Social Sciences Research Journal, 2020)
Purpose. If nurses should respect resident´s autonomy, nurses themselves must experience empowerment and respect for their own autonomy in the work environment. The purpose of this study is to get a deeper understanding of nurses’ perception of their own empowerment in the organization’s culture during an intervention program for strengthening autonomy. Design/methodology/approach. Guided semi-structured interviews and moderated group discussions were conducted before and after the intervention. A structured and evaluative content analysis of the text material were performed. Findings. In total 73 nurses and nurse aids working at frontline with the residents were voluntarily included into the study. New categories for nurses’ perceived empowerment and organizational culture could be derived from the text material. Originality/value. The study’s results deliver a theoretical model with a sophisticated system of categories for organizational culture as perceived by nurses that can be used for further qualitative and quantitative research and for a sustainable organization development.